Interactions between physiology and behaviour provide insights into the ecological role of venom in Australian funnel-web spiders: Interspecies comparison - Duran, Linda Hernández; Wilson, David Thomas; Salih, Mohamed; Rymer, Tasmin Lee (PLOS ONE, 2023)
Australian funnel-web spiders are iconic species, characterized as being the most venomous spiders in the world. They are also valued for the therapeutics and natural bioinsecticides potentially hidden in their venom molecules. Although numerous biochemical and molecular structural approaches have tried to determine the factors driving venom complexity, these approaches have not considered behaviour, physiology and environmental conditions collectively, which can play a role in the evolution, complexity, and function of venom components in funnel-webs. This study used a novel interdisciplinary approach to understand the relationships between different behaviours (assessed in different ecological contexts) and morphophysiological variables (body condition, heart rate) that may affect venom composition in four species of Australian funnel-web spiders. We tested defensiveness, huddling behaviour, frequency of climbing, and activity for all species in three ecological contexts: i) predation using both indirect (puff of air) and direct (prodding) stimuli; ii) conspecific tolerance; and iii) exploration of a new territory. We also assessed morphophysiological variables and venom composition of all species. For Hadronyche valida, the expression of some venom components was associated with heart rate and defensiveness during the predation context. However, we did not find any associations between behavioural traits and morphophysiological variables in the other species, suggesting that particular associations may be species-specific. When we assessed differences between species, we found that the species separated out based on the venom profiles, while activity and heart rate are likely more affected by individual responses and microhabitat conditions. This study demonstrates how behavioural and morphophysiological traits are correlated with venom composition and contributes to a broader understanding of the function and evolution of venoms in funnel-web spiders.